2.1: Invited Paper: 16.9‐Inch Flexible AMOLED Display with High Performance Top Gate Oxide TFT. (26th August 2021) - Hsu, YuanJun; Lin, Zhenguo; Lu, Yihong; Han, BaiXiang; Cao, Weiran; Wu, Yuan-chun; Zhang, Xin
Abstract : We have fabricated top‐gate IGZO TFTs on PI substrate, which exhibit excellent electrical properties and high mechanical reliabilities to meet the demand for large area flexible display. The ΔVth under PBTS and NBTIS for 10 hours are only +0.26 V and −0.34 V, respectively. The mechanical bending properties of the TFT backplane is investigated. There are almost no change after 200, 000 bending cycle test at a curvature radius of 20mm. To improve flexible capability and reduce cost of flexible OLED display, integrated gate driver on array (GOA) circuits with spilt channel structure has been investigated. Finally, we successfully realize 16.9‐inch rollable OLED display with high performance top gate IGZO TFT and GOA circuits